2014
DOI: 10.1007/s40609-014-0006-9
|View full text |Cite
|
Sign up to set email alerts
|

Conflict and Migration: The Case of Somali Refugees in Northeastern Kenya

Abstract: The Dadaab refugee camp was established in 1991 to accommodate Somali refugees fleeing the ongoing violence, environmental and social problems caused by civil war, famine, and drought. The camp is located in Garissa County in the Northeastern region of Kenya. Recent data indicate that the current population of Dadaab camp (463, 422) is more than five times the camp's recommended initial capacity of 90,000 people. This influx of refugees into Northeastern Kenya has stressed local resources within the region and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…The male FDMNs had issues mainly in relation to discrimination, lack of employment opportunity, physical/verbal abuse, and insecurity. These findings are similar to the findings of previous studies which reported the problems and issues among the refugees and illegal migrants [1,15,[24][25][26][27]. While women of refugee and asylum seeker background face several challenges to health care, a systematic review by Helen et al (2020) reported that the community based intervention approaches are possible and are promising in addressing the problems of women, mothers, neonates and children [28].…”
Section: Discussionsupporting
confidence: 89%
“…The male FDMNs had issues mainly in relation to discrimination, lack of employment opportunity, physical/verbal abuse, and insecurity. These findings are similar to the findings of previous studies which reported the problems and issues among the refugees and illegal migrants [1,15,[24][25][26][27]. While women of refugee and asylum seeker background face several challenges to health care, a systematic review by Helen et al (2020) reported that the community based intervention approaches are possible and are promising in addressing the problems of women, mothers, neonates and children [28].…”
Section: Discussionsupporting
confidence: 89%
“…The most prevalent problem facing women in camps is GBV. GBV can occur from the threat of both strangers and family members and is a symptom of larger overarching issues within the camp that exacerbate women's safety, such as poor infrastructure and lack of security, to name a few (Kumssa, 2014). Consequently, GBV is not an isolated issue, despite the fact that it "remains largely under-reported and unrecognized among refugee … populations" (Vu et al, 2017).…”
Section: Refugee Womenmentioning
confidence: 99%
“…The new and imposing structure within the camp that shifts power from the men of the family to the camp staff may be perceived as oppressive and threaten the man's sense of identity, thus potentially leading him to act out against the women in their communities. Another way women experience GBV in Dadaab is when they are required to fetch firewood and food rations in unsafe and far-off places (Kumssa, 2014). The UNHCR had not always provided the means for gathering firewood at a central locality within the complex grounds.…”
Section: Refugee Womenmentioning
confidence: 99%
“…Far from home, far from safe 7 lack the financial means to pay bribes (Yusef 2014) or simply because they are perceived as taking resources that should first go to Kenyan citizens (Kumssa et al 2014). As we undertook our research, we expected that refugee children residing in Nairobi would also tell of having experienced violence, including by state officials.…”
Section: Or Theymentioning
confidence: 99%